La cobertura forestal en las áreas protegidas de Costa Rica entre 1986/7 y 1996/7 - Calvo, Julio; Quesada, Carlos; Sánchez, Arturo; González, Pablo; Watson, Vicente; Bolaños, Rafael (Revista de Ciencias Ambientales, 1999)
No disponible/Not available